Determinan struktur modal dengan firm size sebagai variabel moderasi - Raihani Raihani; Agustinus Kismet Nugroho Jati (Universitas Hayam Wuruk Perbanas, 2022)
This study aims to determine the effect of tangibility, growth, profitability, and liquidity either partially or simultaneously on the capital structure with firm size as a moderating variable in automotive & component companies. The number of populations are all of automotive & component companies which are listed in Indonesia Stock Exchange 2014-2020. Multiple regression analysis and moderated regression analysis (MRA) used as analysis techniques and Purposive sampling used as sampling method. The result of this study shows that partially growth has significant positive effect on capital structure, while tangibility, profitability, and liquidity has a significant negative effect on capital structure. However, firm size is not able to moderate the effect of tangibility, growth, profitability and liquidity on capital structure. . The implication of this research to regard tangibility, profitability, liquidity and growth, because it’s can affect capital structure.